A mobility support method based on ELM prediction for named data networking - Hua QU; Yansong LI; Jihong ZHAO; Dongxu ZHAO; Jianlong ZHAO (Dianxin kexue)
Named data networking (NDN) is a new generation network architecture under the guidance of information center network,and the mobility support method is the main research point in NDN.In the traditional way of the producer-side mobility support method,the post-response mode is adopted,which makes it impossible to realize the transparency of the switching process.A mobility support method called PB based on ELM prediction was proposed.In the method,the original forwarding interest base was modified and a new control message packet was added so that the corresponding node in the network could adjust the result of the prediction algorithm in advance,and the switch of the producer terminal could respond to the interest package at any time by means of interest packet multicast.At the same time,the method provided a way to quickly restore the original state of the network for the problem that the prediction may fail.The simulation results show that the proposed PB mobility support method can reduce the handoff latency and the packet loss caused by handoff compared with the RP and IP mobility support methods.